Impact of Cry1Ac soybean (Glicine max) on biological and reproductive cycles and herbivory capacity of Spodoptera cosmioides and Spodoptera eridania (Lepidoptera: Noctuidae) - Lutz, Alejandra (2024)
Increasing populations of Spodoptera cosmioides (Walker) and Spodoptera eridania(Stoll) have recently been detected in soybean crops in central Argentina. Besides being polyphagous, these species tolerate the Cry1Ac insecticidal toxin, expressed by genetically modified Bt soybean (MON89788 x MON87701). Consequently, when facing big populations, farmers often apply insecticides. This study aimed to determine the effects of Bt soybean on the consumption, biological cycle, and reproduction of both Spodoptera species. Larval feeding on Bt soybean led to a shorter pupal period (23% less than control) and a decreased leaf-area consumption for S. cosmioides (14% less than the non-Bt soybean). In S. eridania,the larval stage, adult longevity, larva-to-adult,and oviposition periods were reduced (11, 23, 13, and 30% shorter than control, respectively). Despite these reductions, both Lepidoptera species completed their reproductive cycles. These valuable findings help us understand the biology of these potential pests in Bt soybean crops in Argentina.